Anti-parasite activity of novel 3,5-diiodophenethyl-benzimides (2019)
ABSTRACT: Novel iodotyramides with para-substituted benzoic acids were synthesized via electrophilic aromatic substitutions and amide coupling via N,N’-diisopropylcarbodiimide (DIC) in dimethylformamide (DMF). All derivatives were in vitro screened against U-937 macrophages and Plasmodium falciparum, Leishmania panamensis and Trypanosoma cruzi protozoan parasites. The hemolytic activity was evaluated on human red blood cells (RBC). Compounds N-(4-hydroxy-3,5-diiodophenethyl)-4-methylbenzamide and N-(3,5-diiodo4-methoxyphenethyl)-4-methoxybenzamide were the most active against L. panamensis with an effective concentration 50 (EC50) of 17.9 and 17.5 μg mL-1, respectively; while compounds N-(3,5-diiodo-4-methoxyphenethyl)-4-methylbenzamide and N-(3,5-diiodo-4-methoxyphenethyl)- 4-methoxybenzamide were the most active for T. cruzi with EC50 values of 23.75 and 6.19 μg mL-1 , respectively. In contrast, all derivatives showed high activity against P. falciparum with EC50 < 25 μg mL-1, except compound N-(4-hydroxy-3,5-diiodophenethyl)-benzamide. No compound was hemolytic over RBC. This report represents the importance of novel iodotyramides as anti-parasites agents.